(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kasmiati, Latuconsina N, Putri AA, Khasanah R, Nurfaidah, Fahrul, Syahrul, Metusalach. 2022. Species determination and heavy metal content of sailfin catfish (Pterygoplichthys pardalis) from Tempe Lake, South Sulawesi, Indonesia. Biodiversitas 23: 4409-4417. Sailfin catfish is invasive alien species that has become dominant in Indonesian freshwater, including in Tempe Lake, South Sulawesi, Indonesia. Despite their abundance, these sailfin catfish are not utilized because of suspicions that they are contaminated by heavy metals that can endanger human health. The purposes of this study were to determine the sailfin catfish species present in Tempe Lake and measure the content of heavy metals Hg, Pb, and Cd in various body parts. Fish species were identified based on abdominal patterns, while heavy metal content was meaured by atomic absorption. The heaviest two body parts were the head (34.04%) and flesh (26.64%), heavy metal content detected in the liver (0.0402-0.0928 mg/kg), gut (0.0322-0.0671 mg/kg), gills (0.319-0.0865 mg/kg), dark meat (0.0268-0.0589 mg/kg), white meat (0.0221-0.0470 mg/kg), bones (0.0180-0.0519 mg/kg), and skin/scales (0.0257-0.0675 mg/kg). All of them were below the FAO/WHO 1989, US-EPA 1999, and the Indonesian National Standards. The government health and safety guidelines for fish to be safe for human consumption were Hg <0.005 mg/kg, Pb<0.10 mg/kg and Cd<0.02 mg/kg. Therefore the abundant sailfin catfish Pterygoplichthys pardalis in Tempe Lake could be consumed directly and as ingredients in other food products.